The philosophy of Hinduism and other essays - Radhakrishnan, Sarvepalli (Motilal Banarsidass, 2011)
The philosophy of Hinduism -- The Hindu dharma -- Islam and Indian thoughts -- Hindu thought & Christian doctrine -- Buddhism -- Indian philosophy